Operational research models in warehouse design and planning - Geraldes, Carla A.S. (2010)
The design and operation of a warehouse involve many challenging decision problems. In this paper, a literature review on warehousing models is presented. Authors start with a hierarchy of decision problems encountered in setting up warehouse design and planning processes. Next, some operational research decision models and solution algorithms supporting decision making at each discussed level are presented. The aim is to link academic researchers and warehouse practitioners, explaining what planning models and methods are currently available for warehouse design and planning, and what are the future research opportunities.